PEMBERDAYAAN KELOMPOK TANI ORGANIK DI KABUPATEN BANTAENG - Muh. Nasir; Muhlis Madani; Anwar Parawangi (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2021)
This study aims to analyze to describe the implementation of farmer empowerment, capacity, government capacity in empowerment used in organic farmers and to describe knowledge, development, and empowerment of organic farmers. This research method is a qualitative approach by analyzing all data and information sourced from primary and secondary data with interview and observation techniques in the Biangloe Village, Pajukukang District, Bantaeng Regency, the Agriculture Service Food Security Service of Bantaeng Regency. The results showed that the support program for empowerment of groups of farmers / organic farmers had knowledge, skills in organic rice farming, the abilities that had been obtained had a positive impact on farmers, on the aspect of saving on organic fertilizer financing, improved rice production which was supported by the adoption of planting patterns, prices the promising organic rice, the health side is safer. Several policy aspects in the development of organic rice farming are referred to here. The first aspect; The sustainability of either the national standard or the standard operating language for organic procedures does not have legality, meaning that the government is still in the inland process for assistance that will be provided to organic farmers, both guidance and supervision as well as competent institutions that will be involved. The second aspect; Farmer group institutions have not contributed much in the planning process of organic rice farmer activities in villages and are more focused on inorganic agriculture, but on the other hand, the RPJMDes dominance has been included in the document even though the realization is still considered unsatisfactory for all parties. Prime program planning can still be improved, its coordination and scope can be expanded across SKPD networks across actors / agencies, planning program needs to support organic farming in villages and in general Bantaeng Regency.